Protecting LGBT+ persons in Africa from torture: Challenges, opportunities, and comparative experiences - Renata Politi; Chris Esdaile (Torture)
This news piece is about REDRESS' webinar held on 1 July 2021 on the protection of LGBT+ persons in Africa from torture and ill-treatment. The speakers on that occasion included (i) Victor Madrigal, the UN Independent Expert on protection against violence and discrimination based on sexual orientation and gender identity; (ii) Sibongile Ndashe, founder and Executive Director of the Initiative for Strategic Litigation in Africa (ISLA), based in South Africa; Ayo Sogunro, Manager of the Sexual Orientation, Gender identity and Sex Characteristics Unit at the Centre for Human Rights of the University of Pretoria, in South Africa; and (iv) Gabriela Oporto, from the Peruvian organisation PROMSEX.